High-volume solid water-based epoxy zinc-rich primer and preparation method thereof
By using combination components such as amphiphilic polysiloxane hollow microspheres in aqueous epoxy zinc-rich coatings, the problem of low solid content in the primer of the water-based epoxy zinc-rich coating is solved, and efficient and environmentally friendly anticorrosion coating construction is achieved, and construction efficiency and corrosion resistance are improved.
Patent Information
- Application Number
- CN202411975389.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The volume of the existing water-based epoxy zinc-rich coating primer is relatively low, and multiple spraying processes are required to meet the design film thickness, resulting in a reduced construction efficiency and increased energy consumption, and the added inorganic filler leads to a decrease in the anti-corrosion performance of the paint film.
Using amphiphilic polysiloxane hollow microspheres, a high volume solid aqueous epoxy zinc-rich primer was prepared by modifying the combination of epoxy resin, dispersant, defoaming agent, cosolvent, zinc powder, rheology additive, anti-rust filler and epoxy curing agent.
It effectively improves the volume and solid content of the paint, reduces the number of construction times, improves construction efficiency and corrosion resistance, and also improves the toughness and strength of the coating film.
Smart Images

Figure CN119775858A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of anti-corrosion coatings, and in particular to a high-volume solid water-based epoxy zinc-rich primer and a preparation method thereof. Background Art
[0002] Waterborne zinc-rich epoxy is a kind of green high-performance anti-corrosion coating that has been widely used in recent years. It can replace solvent-based zinc-rich epoxy, hot-dip galvanizing, etc. It can achieve the same anti-corrosion effect as solvent-based zinc-rich epoxy and hot-dip galvanizing by spraying at room temperature, avoiding the shortcomings of high pollution and high energy consumption of solvent-based zinc-rich epoxy and hot-dip galvanizing. However, there are also some disadvantages in the application of waterborne zinc-rich epoxy. The density of waterborne zinc-rich epoxy is relatively large, resulting in a low volume solid content. For projects with high film thickness of primer design and construction, a multi-pass spraying process is required to meet the demand of high film thickness. The above phenomenon leads to defects such as reduced construction efficiency and increased energy consumption. Secondly, some coating manufacturers on the market reduce the density of waterborne zinc-rich epoxy primer by adding low-density inorganic fillers, thereby increasing the volume solid content of the coating. However, due to the low resin content, the paint film and the excess inorganic fillers cannot be fully wrapped, resulting in a decrease in the anti-corrosion performance of the paint film and the defect of insufficient flexibility, which ultimately affects its anti-corrosion performance and cannot reach the anti-corrosion life of hot-dip galvanizing and solvent-based zinc-rich epoxy. Summary of the invention
[0003] In order to solve the problem that the existing water-based epoxy zinc-rich paint primer has a low volume solid content and requires multiple spraying processes to meet the designed film thickness, the present invention provides a high volume solid content water-based epoxy zinc-rich primer and a preparation method thereof.
[0004] The technical solution of the present invention is as follows:
[0005] The first object of the present invention is to provide a high volume solid waterborne epoxy zinc-rich primer, the raw materials contained and the weight proportions of each raw material are:
[0006] 10-20 parts of water-soluble modified epoxy resin, 0.5-1 parts of dispersant, 0.1-0.5 parts of defoamer, 5-15 parts of cosolvent, 3-8 parts of amphiphilic polysiloxane hollow microspheres, 40-70 parts of zinc powder, 1-5 parts of rheological additive, 5-20 parts of rust-proof filler and 5-15 parts of epoxy curing agent;
[0007] The specification of the amphiphilic polysiloxane hollow microspheres is D50=300-500 μm, and the wall thickness is 20 μm.
[0008] In one embodiment of the present invention, the preparation method of amphiphilic polysiloxane hollow microspheres is:
[0009] Mix the pH regulator, sodium dodecyl sulfate and water to form an aqueous phase;
[0010] Mixing vinyl siloxane, vinyl monomer, initiator and hexadecanol uniformly to form an oil phase;
[0011] The oil phase is added dropwise into the water phase, and the amphiphilic polysiloxane hollow microspheres are obtained through ultrasonic fine emulsification, centrifugal water washing, anhydrous ethanol washing, and vacuum drying.
[0012] In one embodiment of the present invention, the pH adjuster is one or more of sodium hydroxide, sodium bicarbonate, sodium carbonate, sodium phosphate, sodium dihydrogen phosphate, and potassium hydrogen phosphate.
[0013] In one embodiment of the present invention, the vinyl siloxane is one or more of silane KH-570, vinyl triethoxy silane, and methacryloxypropyl triethoxy silane.
[0014] In one embodiment of the present invention, the vinyl monomer is one or more of methyl methacrylate, styrene, and acrylonitrile.
[0015] In one embodiment of the present invention, the initiator is one or more of azobisisobutyronitrile, benzoyl peroxide, and azobisisoheptylnitrile.
[0016] In one embodiment of the present invention, the preparation method of amphiphilic polysiloxane hollow microspheres is:
[0017] Mix NaHCO3, NaH2PO4, sodium dodecyl sulfate and water to form an aqueous phase;
[0018] Silane KH-570, methyl methacrylate, azobisisobutyronitrile and hexadecanol were mixed evenly to form an oil phase;
[0019] The oil phase is added dropwise into the water phase, and the amphiphilic polysiloxane hollow microspheres are obtained through ultrasonic fine emulsification, centrifugal water washing, anhydrous ethanol washing, and vacuum drying.
[0020] In one embodiment of the present invention, the preparation method of amphiphilic polysiloxane hollow microspheres is:
[0021] 0.1 parts of NaHCO3, 0.1 parts of NaH2PO4, 0.1 parts of sodium dodecyl sulfate and 89 parts of water were added into a flask and mixed to form an aqueous phase; 10 parts of silane KH-570 mixed with methyl methacrylate, 0.1 parts of azobisisobutyronitrile and 0.4 parts of hexadecanol in a certain mass ratio were mixed evenly to form an oil phase;
[0022] The oil phase is added dropwise to the water phase in the flask, and after coarse emulsification by stirring for 0.5 h, ultrasonic fine emulsification (10 min, 25° C.) is performed; the emulsion is polymerized at 75° C. for 6 h, and the polysiloxane hollow microsphere powder is obtained by centrifugal washing; the polysiloxane hollow microsphere powder is washed with anhydrous ethanol, and vacuum dried at 60-75° C. to obtain white powdery amphiphilic polysiloxane hollow microspheres.
[0023] In one embodiment of the present invention, the ultrasonic microemulsification conditions are: ultrasonic treatment at 50000 Hz for 10 min at 25±5°C.
[0024] In one embodiment of the present invention, the water-soluble modified epoxy resin is a water-soluble polyurethane modified epoxy resin, which has a glass transition temperature of 70-80° C. and a molecular weight of 30,000-80,000.
[0025] In one embodiment of the present invention, the dispersant is an aqueous non-ionic polyurethane dispersant.
[0026] In one embodiment of the present invention, the defoaming agent is a polyether defoaming agent.
[0027] In one embodiment of the present invention, the co-solvent is at least two of propylene glycol methyl ether, diethylene glycol butyl ether, isopropanol, propylene glycol methyl ether acetate, and alcohol ester twelve.
[0028] In one embodiment of the present invention, the rheological additive is one or more of bentonite, polyamide wax, polyethylene wax, and fumed silica.
[0029] In one embodiment of the present invention, the rust-proof filler is one or more of iron titanium powder, aluminum tripolyphosphate, zinc phosphate, silicon micropowder, mica iron oxide, and ferrophosphorus powder.
[0030] In one embodiment of the present invention, the epoxy curing agent is one or more of aliphatic amine, alicyclic amine, aromatic amine, and polyamide epoxy curing agent.
[0031] The second object of the present invention is to provide a method for preparing the above-mentioned high volume solid water-based epoxy zinc-rich primer, comprising the following steps:
[0032] (1) Add 10-20 parts of water-soluble modified epoxy resin to 80% of the cosolvent, add 1-5 parts of rheological additive at a speed of 600-800 rpm, stir for 5-10 minutes, and then continue to stir for 30-60 minutes at a speed of 1000-1500 rpm to fully activate;
[0033] (2) adding 0.5-1 parts of dispersant to the product treated in step (1), and then adding to the remaining 20% of the cosolvent, and then adding 40-70 parts of zinc powder and 5-20 parts of antirust filler in sequence, stirring at a speed of 800-1000 rpm until the particle size of the mixed solution is less than 65 μm, and finally adding 3-8 parts of amphiphilic hollow polysilicone microspheres, stirring until uniform, as the main agent of high volume solid content water-based epoxy zinc-rich primer;
[0034] (3) Take 5-15 parts of epoxy curing agent and mix them evenly with the above-mentioned water-based epoxy zinc-rich primer main agent to obtain a high volume solid water-based epoxy zinc-rich primer.
[0035] The beneficial technical effects of the present invention are:
[0036] The hollow polysiloxane microspheres in the present invention have a relatively low density due to their hollow structure. When added to water-based epoxy zinc-rich, they can effectively reduce the specific gravity of the coating and increase the volume solid content. Secondly, the synthesis steps are simple and easy to obtain, the particle size is adjustable, and the structure has water-oil amphiphilicity. In the coating dispersion stage, its lipophilicity can help it to be well integrated into the water-soluble system and is stable in storage. In the paint preparation stage, its hydrophilicity can improve the emulsification of the coating and help the coating to be diluted with water. The relatively low particle size enables the hollow polysiloxane microspheres to be well wrapped by the resin and fill the gaps in the coating film. When the coating film is stressed, the hollow structure absorbs the stress, enhances the toughness and strength of the coating film, and improves the crack resistance of the coating film.
[0037] The present invention is based on a water-soluble polyurethane modified epoxy resin, which forms a strong bond energy with the substrate to be protected and the zinc powder. The coating has a short drying time, and the formed coating film has an adhesion of more than 5MPa, an impact resistance of more than 50g / cm, a water resistance of more than 4000h, a salt water resistance of more than 3000h, a moisture and heat resistance of more than 2000h, and a salt spray resistance of more than 10000h. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 Schematic diagram of the preparation process of amphiphilic polysiloxane hollow microspheres. DETAILED DESCRIPTION
[0039] The present invention is described in detail below in conjunction with the accompanying drawings and embodiments.
[0040] In the embodiment of the present invention, a 330 type water-soluble polyurethane modified epoxy resin with an epoxy equivalent of 600-700 is used, which is purchased from Lian Gu New Material Technology Co., Ltd.
[0041] The dispersant is a water-based non-ionic polyurethane dispersant 7456F, which was purchased from Guangzhou Siluoke New Materials Co., Ltd.
[0042] The cosolvent is obtained by mixing diethylene glycol butyl ether and propylene glycol methyl ether in a mass ratio of 1:1.
[0043] The zinc powder is 800 mesh zinc powder, with a total zinc content of 99.9% and a metallic zinc content of more than 98%, and a particle size of ≤40μm. It is purchased from Hunan Xinweiling Metal New Materials Technology Co., Ltd.
[0044] The epoxy curing agent is polyamide curing agent 772, with an active hydrogen equivalent of 150 and a viscosity of 8000-18000 mPas, which was purchased from Liangu New Material Technology Co., Ltd.
[0045] Figure 1 Schematic diagram of the preparation process of amphiphilic hollow polysiloxane microspheres, in which the groups on the surface of the hollow polysiloxane microspheres are silanol (Si-OH) or silanol methoxy (Si-OCH3).
[0046] Example 1
[0047] A method for preparing amphiphilic polysiloxane hollow microspheres comprises the following steps:
[0048] 0.1 parts of sodium bicarbonate, 0.1 parts of sodium dihydrogen phosphate, 0.1 parts of sodium dodecyl sulfonate and 89 parts of water are added to a flask; then 7 parts of silane KH-570 are evenly mixed with 3 parts of methyl methacrylate, 0.1 parts of azobisisobutyronitrile and 0.4 parts of hexadecanol, and the mixed solution is added dropwise to the flask, and after stirring for 0.5 hours for coarse emulsification, ultrasonic fine emulsification (10 minutes, 25°C) is performed; polymerize at 75°C for 6 hours to obtain an emulsion, and obtain polysiloxane hollow microsphere powder by centrifugal washing; the polysiloxane hollow microsphere powder is washed with anhydrous ethanol, and vacuum dried at 75°C to obtain white powdery polysiloxane hollow microspheres.
[0049] Example 2
[0050] 0.1 parts of sodium bicarbonate, 0.1 parts of sodium dihydrogen phosphate, 0.1 parts of sodium dodecyl sulfonate and 87 parts of water are added to a flask; then 6 parts of vinyl triethoxysilane are mixed with 6 parts of styrene, 0.1 parts of azobisisobutyronitrile and 0.4 parts of hexadecanol, and the mixed solution is added dropwise to the flask, and after stirring for 0.5 hours for coarse emulsification, ultrasonic fine emulsification (10 minutes, 25°C) is performed; polymerize at 75°C for 6 hours to obtain an emulsion, and obtain polysiloxane hollow microsphere powder by centrifugal washing; the polysiloxane hollow microsphere powder is washed with anhydrous ethanol, and vacuum dried at 60°C to obtain white powdery polysiloxane hollow microspheres.
[0051] Example 3
[0052] 0.1 parts of sodium bicarbonate, 0.1 parts of sodium dihydrogen phosphate, 0.1 parts of sodium dodecyl sulfonate and 88 parts of water are added into a flask; then 4 parts of silane KH-570 are uniformly mixed with 7 parts of acrylonitrile, 0.1 parts of benzoyl peroxide and 0.6 parts of hexadecanol, and the mixed solution is added dropwise into the flask, and after being stirred for 0.5 hours for coarse emulsification, ultrasonic fine emulsification (10 minutes, 25°C) is performed; polymerize at 75°C for 6 hours to obtain an emulsion, and obtain polysiloxane hollow microsphere powder by centrifugal washing; the polysiloxane hollow microsphere powder is washed with anhydrous ethanol, and vacuum dried at 70°C to obtain white powdery polysiloxane hollow microspheres.
[0053] Example 4
[0054] 0.1 parts of sodium bicarbonate, 0.1 parts of potassium hydrogen phosphate, 0.1 parts of sodium dodecyl sulfonate and 88 parts of water are added into a flask; then 9 parts of methacryloyloxypropyl triethoxysilane are mixed evenly with 2 parts of styrene, 0.1 parts of azobisisoheptanenitrile and 0.6 parts of hexadecanol, and the mixed solution is added dropwise into the flask, and after coarse emulsification by stirring for 0.5 hours, ultrasonic fine emulsification (10 minutes, 25°C) is performed; polymerize at 75°C for 6 hours to obtain an emulsion, and obtain polysiloxane hollow microsphere powder by centrifugal washing; the polysiloxane hollow microsphere powder is washed with anhydrous ethanol, and vacuum dried at 75°C to obtain white powdery polysiloxane hollow microspheres.
[0055] Example 5
[0056] A high volume solid content water-based epoxy zinc-rich primer, comprising the following components by weight: 13 parts of water-soluble polyurethane modified epoxy resin, 0.5 parts of dispersant, 6.5 parts of cosolvent, 4.5 parts of polysiloxane hollow microspheres, 63 parts of zinc powder, 2.5 parts of rheological additive, 10 parts of anti-rust filler and 10 parts of epoxy curing agent;
[0057] The preparation method comprises the following steps:
[0058] (1) Weigh each component according to mass fraction;
[0059] (2) Take 5.5 parts of co-solvent, add 13 parts of epoxy resin to the co-solvent, stir at 600 r / min for 20 min, add 2.5 parts of rheological additive while stirring after mixing evenly, continue stirring to fully activate;
[0060] (3) adding 0.5 parts of dispersant to step (2), adding the remaining 1 part of cosolvent after stirring, and then adding 63 parts of zinc powder, 6 parts of iron titanium powder and 4 parts of aluminum tripolyphosphate in sequence, accelerating stirring until the particle size of the mixed solution is less than 65 μm, and finally adding polysiloxane hollow microspheres to obtain a high volume solid content water-based epoxy zinc-rich primer component A;
[0061] (4) 10 parts of epoxy curing agent are taken to prepare component B of high volume solid content water-based epoxy zinc-rich primer, and component A and component B are evenly mixed to obtain high volume solid content water-based epoxy zinc-rich primer.
[0062] Example 6
[0063] A high volume solid content water-based epoxy zinc-rich primer, comprising the following components by weight: 18 parts of water-soluble polyurethane modified epoxy resin, 0.5 parts of dispersant, 1.5 parts of cosolvent, 6 parts of polysiloxane hollow microspheres, 63 parts of zinc powder, 2.5 parts of rheological additive, 8 parts of anti-rust filler and 10 parts of epoxy curing agent;
[0064] The preparation method is the same as Example 5.
[0065] Example 7
[0066] A high volume solid content water-based epoxy zinc-rich primer, comprising the following components by weight: 10 parts of water-soluble polyurethane modified epoxy resin, 0.5 parts of dispersant, 8.5 parts of cosolvent, 9 parts of polysiloxane hollow microspheres, 63 parts of zinc powder, 2.5 parts of rheological additive, 8.5 parts of anti-rust filler and 10 parts of epoxy curing agent;
[0067] The preparation method is the same as Example 5.
[0068] Example 8
[0069] A high volume solid content water-based epoxy zinc-rich primer, comprising the following components by weight: 10 parts of water-soluble polyurethane modified epoxy resin, 0.5 parts of dispersant, 4.5 parts of cosolvent, 10 parts of polysiloxane hollow microspheres, 70 parts of zinc powder, 2.5 parts of rheological additive, 2.5 parts of anti-rust filler and 10 parts of amine curing agent;
[0070] The preparation method is the same as Example 5.
[0071] Comparative Example 1
[0072] A high volume solid content water-based epoxy zinc-rich primer, comprising the following components by weight: 13 parts of water-soluble polyurethane modified epoxy resin, 0.5 parts of dispersant, 6.5 parts of cosolvent, 63 parts of zinc powder, 2.5 parts of rheological additive, 14.5 parts of anti-rust filler and 10 parts of epoxy curing agent;
[0073] The preparation method is the same as Example 5.
[0074] Comparative Example 2
[0075] A high volume solid content water-based epoxy zinc-rich primer, comprising the following components by weight: 13 parts of water-soluble polyurethane modified epoxy resin, 0.5 parts of dispersant, 6.5 parts of cosolvent, 4.5 parts of commercially available hydrophilic hollow glass microspheres, 63 parts of zinc powder, 2.5 parts of rheological additive, 10 parts of anti-rust filler and 10 parts of epoxy curing agent;
[0076] The preparation method is the same as Example 5.
[0077] Comparative Example 3
[0078] A high volume solid content water-based epoxy zinc-rich primer, comprising the following components by weight: 13 parts of water-soluble polyurethane modified epoxy resin, 0.5 parts of dispersant, 6.5 parts of cosolvent, 4.5 parts of commercially available oleophilic hollow glass microspheres, 63 parts of zinc powder, 2.5 parts of rheological additive, 10 parts of anti-rust filler and 10 parts of epoxy curing agent;
[0079] The preparation method is the same as Example 5.
[0080] Comparative Example 4
[0081] A high volume solid content water-based epoxy zinc-rich primer, comprising the following components by weight: 13 parts of water-soluble epoxy resin, 0.5 parts of dispersant, 6.5 parts of cosolvent, 4.5 parts of polysiloxane hollow microspheres, 63 parts of zinc powder, 2.5 parts of rheological additive, 10 parts of anti-rust filler and 10 parts of epoxy curing agent;
[0082] The preparation method is the same as Example 5.
[0083] Comparative Example 5
[0084] A high volume solid waterborne epoxy zinc-rich primer, comprising the following components by weight: 13 parts of water-soluble epoxy resin, 0.5 parts of dispersant, 6.5 parts of cosolvent, 63 parts of zinc powder, 2.5 parts of rheological additive, 14.5 parts of anti-rust filler and 10 parts of epoxy curing agent;
[0085] The preparation method is the same as Example 5.
[0086] The performance of the high volume solid water-based epoxy zinc-rich primer obtained in Example 5 and Comparative Examples 1-4 was tested, and the results are shown in Table 1.
[0087] Table 1
[0088]
[0089] From the results in Table 1, it can be seen that the high volume solid content water-based epoxy zinc-rich primer obtained by the preparation method of the present invention in Example 5 has excellent adhesion, a volume solid content of more than 70%, and an improved coating rate and construction efficiency; at the same time, due to the addition of amphiphilic polysiloxane hollow microspheres, the storage stability of the coating is guaranteed, and good construction performance is guaranteed, and the salt spray resistance can reach more than 2000hr. It has excellent anti-corrosion performance.
[0090] In Comparative Example 1, polysiloxane hollow microspheres were not added, and the coating had a higher specific gravity, with a volume solid content of only 49%. Under the same film thickness conditions, the construction period needed to be increased by nearly 30%. On the other hand, since there was no hollow microsphere structure in the system, the shrinkage stress of the epoxy system during film formation could not be completely released, resulting in poor impact strength and thick film crack resistance.
[0091] Comparative Example 2 uses commercially available hydrophilic hollow glass microspheres, which also have a significant effect in reducing specific gravity and increasing volume solid content. However, due to the large particle size of the hollow glass microspheres, the resin cannot completely wrap the powder under the same addition amount, resulting in a certain decrease in anti-corrosion performance. On the other hand, since the main paint is a water-soluble system, the pure hydrophilic microspheres have poor compatibility with the system, resulting in poor storage stability, and precipitation occurs after one week of hot storage.
[0092] Comparative Example 3 uses commercially available lipophilic hollow glass microspheres, which have good compatibility in water-soluble systems. However, since water dilution is required during construction, the compatibility is poor, the viscosity is high, and the atomization of airless spraying is poor.
[0093] In Comparative Example 4, ordinary water-based epoxy resin is used. Since the flexibility and anti-corrosion performance of ordinary epoxy resin are obviously insufficient compared with polyurethane modified epoxy resin,
[0094] In Comparative Example 5, no polysiloxane hollow microspheres or water-soluble polyurethane-modified epoxy resin was added, and the volume solid content was less than 50%, so the construction efficiency was greatly reduced, the water resistance and salt spray resistance of the coating were significantly reduced, and the coating was prone to cracking.
[0095] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.
Claims
1. A high volume solid waterborne epoxy zinc-rich primer, characterized in that: The raw materials and weight proportions of each raw material are as follows: 10-20 parts of water-soluble modified epoxy resin, 0.5-1 parts of dispersant, 0.1-0.5 parts of defoamer, 5-15 parts of cosolvent, 3-8 parts of amphiphilic polysiloxane hollow microspheres, 40-70 parts of zinc powder, 1-5 parts of rheological additive, 5-20 parts of rust-proof filler and 5-15 parts of epoxy curing agent; The specification of the amphiphilic polysiloxane hollow microspheres is D50=300-500 μm, and the wall thickness is 20 μm.
2. The high volume solid water-based epoxy zinc-rich primer according to claim 1, characterized in that: The preparation method of amphiphilic polysiloxane hollow microspheres is as follows: Mix the pH regulator, sodium dodecyl sulfate and water to form an aqueous phase; Mixing vinyl siloxane, vinyl monomer, initiator and hexadecanol uniformly to form an oil phase; The oil phase is added dropwise into the water phase, and the amphiphilic polysiloxane hollow microspheres are obtained through ultrasonic fine emulsification, centrifugal water washing, anhydrous ethanol washing, and vacuum drying.
3. The high volume solid waterborne epoxy zinc-rich primer according to claim 2, characterized in that: The pH adjuster is one or more of sodium hydroxide, sodium bicarbonate, sodium carbonate, sodium phosphate, sodium dihydrogen phosphate, and potassium hydrogen phosphate; the vinyl siloxane is one or more of silane KH-570, vinyl triethoxysilane, and methacryloxypropyl triethoxysilane; the vinyl monomer is one or more of methyl methacrylate, styrene, and acrylonitrile; the initiator is one or more of azobisisobutyronitrile, benzoyl peroxide, and azobisisoheptonitrile.
4. The high volume solid waterborne epoxy zinc-rich primer according to claim 2, characterized in that: The ultrasonic emulsification conditions were as follows: ultrasonic treatment at 50000 Hz for 10 min at 25±5°C.
5. The high volume solid waterborne epoxy zinc-rich primer according to claim 1, characterized in that: The water-soluble modified epoxy resin is a water-soluble polyurethane modified epoxy resin, the glass transition temperature of which is 70-80°C and the molecular weight is 30,000-80,000.
6. The high volume solid waterborne epoxy zinc-rich primer according to claim 1, characterized in that: The dispersant is an aqueous nonionic polyurethane dispersant; the defoamer is a polyether defoamer; and the cosolvent is at least two of propylene glycol methyl ether, diethylene glycol butyl ether, isopropanol, propylene glycol methyl ether acetate, and alcohol ester twelve.
7. The high volume solid waterborne epoxy zinc-rich primer according to claim 1, characterized in that: The rheological additive is one or more of bentonite, polyamide wax, polyethylene wax and fumed silica.
8. The high volume solid waterborne epoxy zinc-rich primer according to claim 1, characterized in that: The rust-proof filler is one or more of iron titanium powder, aluminum tripolyphosphate, zinc phosphate, silicon micropowder, mica iron oxide, and ferrophosphorus powder.
9. The high volume solid waterborne epoxy zinc-rich primer according to claim 1, characterized in that: The epoxy curing agent is one or more of aliphatic amine, alicyclic amine, aromatic amine and polyamide epoxy curing agent.
10. A method for preparing the high volume solid waterborne epoxy zinc-rich primer according to claim 1, characterized in that: The steps include: (1) Add 10-20 parts of water-soluble modified epoxy resin to 80% of the cosolvent, add 1-5 parts of rheological additive at a speed of 600-800 rpm, stir for 5-10 minutes, and then continue to stir for 30-60 minutes at a speed of 1000-1500 rpm to fully activate; (2) adding 0.5-1 parts of dispersant to the product treated in step (1), and then adding to the remaining 20% of the cosolvent, and then adding 40-70 parts of zinc powder and 5-20 parts of antirust filler in sequence, stirring at a speed of 800-1000 rpm until the particle size of the mixed solution is less than 65 μm, and finally adding 3-8 parts of amphiphilic hollow polysilicone microspheres, stirring until uniform, as the main agent of high volume solid content water-based epoxy zinc-rich primer; (3) Take 5-15 parts of epoxy curing agent and mix them evenly with the above-mentioned water-based epoxy zinc-rich primer main agent to obtain a high volume solid water-based epoxy zinc-rich primer.
Citation Information
Patent Citations
Preparation method of polymer / ZnO / SiO2 nano-composite microspheres
CN105837840A
Method for preparing silicon dioxide hollow microspheres by adopting hard template method
CN116119674A
Water-based cold-spraying alkene zinc coating and preparation method thereof
CN117801639A
Cited By
High-temperature-resistant anticorrosive paint for boiler and preparation method thereof
CN120310378A